Genomic medicine in neurology - Kriti Menon; Divya Agarwal; Dinesh Chaudhari; Pushpendra Nath Renjen (Apollo Medicine)
Introduction: Approximately 80% of genes actively expresses in the brain cells and about 40% of known genetic disorders affect the central nervous system. The advances in the field of genetics and genomics have solved the problem of the diagnostic odyssey in neurological genetic diseases to great extent. The molecular genetic technology has helped in understanding the association of various genetic factors with neurological disorders, filling the gaps in genomic medicine and has led to discovery of novel diseases and their causative genes and helps in providing a multidisciplinary care to the patient and the family. Methods: We have retrospectively evaluated the utility of genetic testing, acceptance of presymptomatic testing, and scope of prevention and management of adult-onset neurological condition in 15 patients from unrelated families, who underwent a minimum of one genetic test to evaluate the genetic basis of their clinical manifestation and/or a positive family history. Results: All of the 15 patients underwent atleast one genetic test. Exome sequencing was the most commonly used molecular test. Definitive diagnoses were obtained for 9/15 families which indicated the diagnostic yield of genetic testing to be around 60% in this patient cohort. A negative or inclusive result was obtained for 6/15 patients with no further genetic testing done. Presymptomatic genetic testing was offered to the extended family members of four families, but none of the family members opted for the same. Prenatal/preimplantation genetic testing options were provided to three families based on the definitive diagnosis obtained from the genetic testing result.